SCAPOLITE-PLAGIOCLASE EXCHANGE: CL-CO3 SCAPOLITE SOLUTION CHEMISTRY AND IMPLICATIONS FOR PERISTERITE PLAGIOCLASE - Rebbert C.R.; Rice J.M. (My University, 1997)
Chemical exchange between coexisting scapolite and plagioclase was studied for both a set of natural pairs from a regionally metamorphosed terrain (450-670°C, 3.5-6 kbar) in northern Idaho and for eight synthetic pairs produced by Ellis (1978) in hydrothermal experiments at 750°C and 4 kbars. On the basis of electron probe microanalysis, the natural scapolite samples exhibit a range of compositions from XEqAn = 0.22, XCl = 0.86 to XEqAn = 0.63, XCl = 0.04, and fall very close to a binary join defined by XCl = -2.046XEqAn + 1.320, r2 = 0.97. The exchange represented by this binary is Na2.4Si1.4Cl # Ca2.4Al1.4CO3. Plagioclase compositions vary fromXAn = 0.0 to 0.44. The distribution coefficient (Kd) for coexisting scapolite and plagioclase compositions was calculated for the equilibrium: 2 anorthite + albite + calcite # CO3-scapoliteSolution modelling based on this equilibrium and comparison of 1n Kd for the natural Idaho pairs with that of the high temperature synthetic pairs indicate nearly ideal solution behavior for observed scapolite compositions. For the Idaho samples with XAn < 0.16, Kd ranges over 10 orders of magnitude. This variation is presumed to result from inadequacies of extrapolating available plagioclase solution models to lower temperatures in the region of the peristerite gap. Assuming nearly ideal scapolite solid solution, we approximate plagioclase activities for XAn < 0.2 at 520°C and 5500 bars by the following solution parameters: WAn = 22.6 kJ/mol and WAb = -12.8 kJ/mol.